Visualisation of historical flood and drought information (1100 - 1940) for the middle reaches of the Yangtze River Valley, P. R. China - Chen, Jiaqi; Gemmer, Marco; Jiang, Tong; King, Lorenz; Metzler, Martin; Justus Liebig University Giessen (My University, 2001)
Due to very uneven distribution of precipitation in space and time, China is frequently affected by floods and droughts. These natural disasters have been a major drawback for the economic and social development in China throughout history. Since the beginning of the 1920s, Chinese scientists have compiled a remarkably good inventory of historical climate data. This data is suitable for the evaluation of extreme climate events and for the creation of climatological long-term models which may allow a prediction regarding the future distribution and availability of water. Thereby, the development of climate factors should be projected into the future, starting from the available climate test series in China, as well as those from the historical proxy data (regarding extreme climate events and their effect, such as floods or droughts). This paper is an introduction to the paleoclimatic research that has been carried out at the Zentrum für internationale Entwicklungs- und Umweltforschung (ZEU) of the Justus Liebig University Giessen in 2000 and 2001. With the research in the Yangtze River Valley it is aimed to assess and analyse historical climatological events in order to interpret flood and drought events in history. Even more important is the sole of this data in the designation of flood prone areas and the magnitude of major climatic events. On the basis of the evaluation of this long-term climatic trend. Predictions about climatic changes can be made.
Keywords: Jangtsekiang; Überschwemmung; Bodenerosion; ddc:650